The Union Wage Effect Re-Examined - Maki, Dennis; Christensen, Sandra (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1980)
In this paper, the authors extend the literature on union wage effect in two ways. They use aggregate industry data in a simultaneous-equations model to provide an estimate for the union wage effect in Canada which recognizes the endogenity of union coverages. And they suggest a possible cause for the difference in results obtained for the U.S. by Ashenfelter and Johnson, on the one hand, and Kahn on the other.